The optical characterization of metal-mediated aggregation behaviour of amphiphilic Zn(II) phthalocyanines - Batat, P.; Bayar, M.; Pur, B.; Coker, E.; Ahsen, V.; Yuksel, F.; Demirel, A. L. (Royal Soc Chemistry, 2016)
Ag+ mediated aggregation behaviour of two different amphiphilic zinc phthalocyanines (Zn-Pcs) (symmetric and asymmetric) has been investigated in solution, at the air-water interface and in Langmuir-Blodgett (LB) films transferred onto glass substrates. A 4 : 1 ([Ag+]/[Pc]) complexation was observed for both symmetric and asymmetric Zn-Pcs at high [Ag+] concentrations which led to the formation of H-aggregates in solution. At the air-water interface, both symmetric and asymmetric Zn-Pcs showed a tilted, edge-on orientation in columnar stacks. Addition of Ag+ to the subphase enhanced the order in the monolayers. LB films on glass substrates showed a split Q-band indicating the presence of herring-bone type aggregation consisting of both H- and J-aggregates. For LB films deposited from a Ag+ containing subphase, a shoulder appeared in the absorption spectra at longer wavelengths which indicates that the fraction of J-aggregates was enhanced by Ag+ in LB films. The molecular orientation in LB films was investigated by polarized absorption spectroscopy and a tilt angle was calculated to be 49 degrees with the substrate normal for symmetric and 74.61 for the asymmetric Zn-Pc. The presence of Ag+ cations in the subphase decreased the tilt angles slightly by 4-5 degrees. These results indicate that Ag+ induced the aggregation of Zn-Pcs and acted as a linker between Pc molecules in the ultrathin films of both symmetric and asymmetric Zn-Pcs. These results are important in inducing J-aggregates for the fabrication of molecular devices based on phthalocyanine thin films.
Keywords: Langmuir-Blodgett-Films; Spectral Properties; Silver(I); Tetrakis(Thiadiazole)Porphyrazines; 1,2,5-Thiadiazole; Complexes; Chemistry; Targets